Genetic and phenotypic parameters of body and muscle weights and abdominal fat in meat-type chicken - SINGH, RANJIT; TREHAN, P K (The Indian Journal of Animal Sciences, 2013)
Estimates of genetic and phenotypic parameters of 6-week body weight, breast, thigh and leg muscle weights and abdominal fat, were obtained by analysing the data on 416 and 448 chicks of 2 broiler-selected lines. 'PB-1' and Â·PB-2'. respectively. from the sire components of variances and covariances_ All the measurements were made at 6 weeks of age. The heritability estimates ranged from moderate 10 high for all the traits. The estimates for muscle weights and abdominal fat were considerably reduced. wheh these were expressed as percentage of body weight. The genetic correlations of body weight with thigh. brcast and leg muscles weight were positive and very high. Genetic correlations among the 3 muscle groups were alsopositive and very high. Body weight was also highly correlated with abdominal fat. The estimates of genetic correlations indicatcd that selection for 6-week body weight would lead to increased deposition of abdominal fat and to desproportionate increase in relative amounts of breast vs leg muscles.